Green Ionic Liquid Lubricants Prepared from Anti-Inflammatory Drug - Song, Zenghong; Yu, Qiangliang; Cai, Meirong; Huang, Guowei; Yao, Meihuan; Li, Dongmei; Liang, Yongmin; Fan, Mingjin; Zhou, Feng (Tribology letters, 2015)
1-Alkyl-3-methylimidazolium ibuprofen ionic liquids (ILs, L-Ibu104, L-Ibu106 and L-Ibu108) were synthesized from an anti-inflammatory drug, sodium ibuprofen. The physicochemical and tribological properties of these ILs as neat lubricants for steel/steel and steel/copper contacts were measured. The results of hydrolysis stability evaluation and copper strip corrosion test show that these kinds of ILs are hydrolysis stable and have no corrosion to the metal contacts because of stability of anion. The friction and wear test results exhibit that these ibuprofen ILs have more effective friction-reducing and anti-wear properties than poly-alpha-olefin (PAO40) and 1-hexyl-3-methylimidazolium bis(trifluoromethylsulphonyl)imide (L-F106) at 100 °C. According to the X-ray photoelectron spectrometer analytical results, we speculated that physical adsorption films can easily formed on the metal worn surfaces during the rubbing process because of the high adsorption ability of Ibu − anion, which play an important role in the good lubricating behaviours of ibuprofen ILs. Graphical Abstract